2001
DOI: 10.1159/000046275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prolonged Corticosteroid Therapy on the Outcome of Steroid-Responsive Nephrotic Syndrome

Abstract: Eighty-six patients (59 males and 27 females) diagnosed with steroid-responsive nephrotic syndrome during childhood were identified. The patients were 20–40 years of age (mean 27.0 ± 5.0) with a mean follow-up period of 19.5 ± 5.9 years. All patients had been treated with a long-term tapering corticosteroid therapy. Thirty patients had also received a course of cyclophosphamide (2 mg/kg/day for 12 weeks). Sixty-six had achieved sustained remission off corticosteroids, while 20 were still receiving corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The reports on delays in growth of children with INS were mainly based on shortterm observations of the patients during steroid therapy [13]. Matsukura et al [14] observed shorter heights in patients with steroid-dependent INS than in those with steroid-sensitive INS. Kitamura [15] found that the final heights of patients with INS treated with GCs during the pubertal body growth spurt were significantly less than the heights of healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reports on delays in growth of children with INS were mainly based on shortterm observations of the patients during steroid therapy [13]. Matsukura et al [14] observed shorter heights in patients with steroid-dependent INS than in those with steroid-sensitive INS. Kitamura [15] found that the final heights of patients with INS treated with GCs during the pubertal body growth spurt were significantly less than the heights of healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…These finding are consistent with known effects of corticosteroids causing growth impairment in adolescents and young adults with frequently relapsing nephrotic syndrome. Matsukura et al found the mean (SD) height Z score of a population of Japanese patients with a mean age of 27.0 years to be −0.43 (1.19), although 20 of the 86 patients were still receiving corticosteroid therapy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Growth impairment is related to the duration and intensity of steroid therapy, and catch-up growth after the cessation of steroid treatment may be partial and irregular [6][7][8][9][10]. Although steroid regimens used in children with SSNS do not usually have a significant impact on growth [6,[11][12][13][14][15], severe growth retardation has been reported in children with steroiddependent or frequently relapsing nephrotic syndrome, especially in boys [13,14,16]. Studies specifically investigating the linear growth of children with severe SDNS treated with long-term CsA and steroid combination therapy are scarce [17,18].…”
Section: Introductionmentioning
confidence: 99%